Effect of anisotropy on the logarithmic singularities in the electronic density of states in layered systems - Digor, Dumitru (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2010)
The electronic density of states was calculated for the case of anisotropic dispersion law